Imbalance of Th1 and Th2 Cytokines and Stem Cell Therapy in Pathological Pain - Yu, Yao-Qing; Wang, Huan (CNS & Neurological Disorders - Drug Targets, 2024)
The pathophysiological importance of T helper 1 (Th1) and Th2 cell cytokines in pathological pain has been highly debated in recent decades. However, the analgesic strategy targeting individual cytokines still has a long way to go for clinical application. In this review, we focus on the contributions of Th1 cytokines (TNF-α, IFN-γ, and IL-2) and Th2 cytokines (IL-4, IL-5, IL-10, and IL-13) in rodent pain models and human pain-related diseases. A large number of studies have shown that Th1 and Th2 cytokines have opposing effects on pain modulation. The imbalance of Th1 and Th2 cytokines might determine the final effect of pain generation or inhibition. However, increasing evidence indicates that targeting the individual cytokine is not sufficient for the treatment of pathological pain. It is practical to suggest a promising therapeutic strategy against the combined effects of Th1 and Th2 cytokines. We summarize the current advances in stem cell therapy for pain-related diseases. Preclinical and clinical studies show that stem cells inhibit proinflammatory cytokines and release enormous Th2 cytokines that exhibit a strong analgesic effect. Therefore, a shift of the imbalance of Th1 and Th2 cytokines induced by stem cells will provide a novel therapeutic strategy against intractable pain. It is extremely important to reveal the cellular and molecular mechanisms of stem cell-mediated analgesia. The efficiency and safety of stem cell therapy should be carefully evaluated in animal models and patients with pathological pain.
Keywords: stem cells